Nanocellulose Production from Empty Palm Oil Fruit Bunches (EPOFB) Using Hydrolysis Followed by Freeze Drying - Hidayatullah, Irwan; Widyanti, Emmanuella Maria; Kusumawati, Endang; Elizabeth, Lidya (ASEAN Journal of Chemical Engineering, 2021)
Empty palm oil fruit bunches (EPOFB) are lignocellulose which is abundantly available in Indonesia. EPOFB has big potential as raw materials to substitute wood in nanocellulose manufacture. The production of nanocellulose from EOPFB consists of various stages, such as preparation by grinding and sizing, α-cellulose isolation, acid hydrolysis, and freeze-drying. α-cellulose isolate from POEFB through delignification using 17.5% NaOH (w / v) at 80oC for 30 minutes and bleaching using 10% H2O2 (v / v) at 70oC for 15 minutes. The bleached cellulose was then hydrolyzed by acid hydrolysis process using 64% H2SO4 for 45 minutes with temperature variations to determine the effect of temperature on the size of nanocellulose. Obtained nanocellulose then dried with the freeze-drying method at a temperature of 50oC for 6 hours. The nanocellulose morphology was characterized using SEM analysis, and FTIR analysis was done to determine the presence of cellulose and lignin. The smallest average diameter obtained at 50oC temperature is 86.8 nm with a 51.5 – 66.5 nm distribution range.